Cryotherapy in the paediatric airway: Indications, success and safety. Issue 11 (28th August 2022) - Schramm, Dirk; Freitag, Nadine; Kötz, Karsten; Iglesias‐Serrano, Ignacio; Culebras‐Amigo, Mario; Koblizek, Vladimir; Pérez‐Tarazona, Santiago; Cases Viedma, Enrique; Srikanta, JT; Durdik, Peter; Darwiche, Kaid; Rubak, Sune; et al.
Abstract: Background and objective: Cryotherapy in interventional bronchoscopy is a new treatment modality, which has recently been made available for the paediatric airway. Lack of experience and safety concerns have led to hesitant adaptation. The aim of this study was to assess indications, success rates and complications of airway cryotherapy in children. Methods: Bronchoscopists from medical centre performing cryotherapy in patients between 0 and 18 years were invited to participate in a prospective study based on an online questionnaire. Patient and participant data were collected between June 2020 and June 2021. Results: A total of 69 cryotherapy procedures were performed in 57 patients a for three main indications: Biopsy (30), restoration of airway patency (23) and foreign body aspiration (16). The overall success rate was 93%, the remaining 7% were performed for foreign body removal and required a switch of technique. Restoration of airway patency was successfully applied in various pathologies, including mucus plugs, bronchial casts and post traumatic stenosis. The diagnostic yield of transbronchial biopsies was 96%. No severe complications were encountered; one pneumothorax following a cryobiopsy required a chest drain for 48 h. No child was admitted to intensive care or died from a procedural complication. Conclusion: In this largest paediatric case collection to date, cryotherapy was safe and carried a high success rate. Cryobiopsy compares favourably to the widely used forceps biopsy and could replace it in the future. Paediatric bronchoscopists are encouraged to add cryotherapy to their armamentarium of airway interventions. Abstract : This largest case collection of cryotherapy procedures in the paediatric airway to date demonstrates that cryotherapy can be safely and successfully applied for cryobiopsy, restoration of airway patency and foreign body removal. Paediatric interventional bronchoscopists are encouraged to add cryotherapy to their armamentarium of airway interventions in the paediatric airway. See related Editorial